Capital Flows and Real Exchange Rates in Emerging Asian Countries - Juthathip Jongwanich (Asian Development Bank (ADB), 2010)
This paper examines the nexus between capital flows and real exchange rate (RER) in emerging Asian countries using a dynamic panel-data model for 2000–2009. In contrast to previous studies, capital flows here are separated into foreign direct investment (FDI), portfolio investment, and other investment (bank loans) flows. Inflows and outflows are also treated separately in the model. The estimation results show that compositions of capital flows matter in determining impacts of the flows on the RER. Portfolio investment and other investment (including bank loans) bring in a faster RER appreciation than FDI. However, the magnitudes of appreciation among capital flows are close to each other. The increasing importance of merger and acquisition activities in FDI makes the flows behave closer to other forms of capital flows, especially portfolio investment. The estimation results also show that capital outflows bring about a greater degree of exchange rate adjustment than capital inflows. All in all, the results imply that the swift rebound of capital flows in the region could result in excessive appreciation of the (real) currencies, especially when capital flows are in a form of portfolio investment and bank loans.
hdl:11540/1948
Keywords: O11; O53; 330; Capital mobility; real exchange rate; emerging Asian countries; FDI; foreign direct investment; Kapitalmobilität; Kaufkraftparität; Auslandsinvestition; Asien